Academic Social Network Sites: Opportunities and Challenges - Mohammad, Mumtazimah; M. Lazim, Yuzarimi; Rosle, Suharmili (International Journal of Engineering and Technology, 2018)
Academic Social Networking Sites (ASNs) have become one of the most important platforms in modern information and education industries. It will definitely become an essential mechanism to communicate, connect and collaborate among the scholarly community. In this paper, we provide a comprehensive investigation of ASNs such as Academia, ResearchGate, Mendeley and Zotero, and identify the features of ASNs. We also discuss the opportunities for ASNs and provide the challenges. Challenges related to ASNs are: collecting relevant data and identifying data quality, finding evaluation metrics and also developing efficient algorithms. Disciplinary differences in domain area and academic position become the opportunities why academicians use ASNs.Â Â